Retail Management: An emerging trend - Sumit Kumar (AG Volumes, 2021)
On the basis of this research, In the retail industry, customer satisfaction is defined as the sensation that a product or service meets or exceeds the expectations of the consumer. For example, damaged or broken goods may be exchanged if the consumer is willing to pay for the return shipping. This research was conducted to determine the link between retail customer service and sales at a retail establishment. In this study, we'll take a look at the various products and services that Indian shops have to offer. Customer satisfaction levels and the influence of retail services on sales are also examined in this research. Finally, there are suggestions on how to provide clients with better retail value added services. As India's economy has been more liberalised, consumers have gained greater buying power, which has fueled retailing's rise in India.